Mobile phone survey: standardization and examination of relation with personality characteristics - Mortan Sevi, Oya; Odabaşıoğlu, Gürkan; Genç, Yasin; Soykal, İlkay; Öztürk, Özgür (Journal of Dependence, 2014)
Objective: The aim of this study is to evaluate the reliability and validity of the Questionnaire for Mobile Phone Survey and to adapt the scale to Turkish sample and also to analyze the relationship between the problematic mobile phone usage and the personality characteristics. (1)Method: CTE consists of 87 items and 7 dimensions, which are socio-demographic information, mobile phone usage of participants, relation of participants with mobile phone, reasons for usage of mobile phone, shopping and purchase, general approach regarding life and personal style. The survey has been applied to 115 persons by means of snowball sampling method. Each participant was made to fill out MMPI accompanied by psychology department senior students, in order to examine the criterion validity of the Survey.Results: Internal consistency has been found quite excessive with Cronbach Alpha coefficient.76. Thecorrelation ofthe Survey’s dimensions with the total score is changing between .34 and .78 (p< 0.01). Increase in usage of mobile phone has been found mostly related to passive-aggressiveness, lack of self-confidence, social withdraw, obsessiveness, dependence or featuring anti-social characteristics, frequently demoralized, experiencing anxiety.Conclusion: It can be stated that CTE is a valid and reliable instrument to evaluate mobile phone usage in the Turkish sample. Furthermore, it can be acknowledged as a successful instrument in researching relation of personality trait with the usage sample. It is considered that extending the samples would be helpful for reaching more generalizable conclusions.
Keywords: mobile phone; dependence; personality; validity; reliability